What college faculty climate assessment reveals about the rewards and challenges of the profession and its relationship to its spirituality - Gutierrez, Angelina (2012)
This research explored the opportunities and challenges of the professoriate in Catholic higher education from the context of the college faculty climate in order to determine the relationship of work satisfaction with spirituality, loyalty and institutional improvement. The method of inquiry used was a triangulation of qualitative, ethnographic and quantitative designs. While the results of the investigation are instructive, the findings are representative only of a small Catholic college and are therefore restricted in utilizing it to other educational settings. This research promotes insights and provocative questions regarding the mutual enhancement of the professoriate and Catholic institutes so that their indispensable contributions in the transformation and renewal of contemporary society may continue flourish.
Keywords: Career development; Employee development; Spirituality